Outdoor leadership theory and practice - Martin, Bruce 1969-; Breunig, Mary 1967-; Goldenberg, Marni 1972-; Wagstaff, Mark 1959- (Human Kinetics, 2017)
Outdoor Leadership, Second Edition, is the definitive text for developing student leadership in outdoor and adventure settings throughout the world. Crafted by an author team internationally recognized for their research, teaching, and experience in outdoor and adventure leadership, this new edition provides students with the foundational knowledge they need to develop as competent professionals in the field. Through Outdoor Leadership, Second Edition, students are introduced to eight core competencies that the authors consider essential to outdoor leadership: 1. Foundational knowledge; 2. Self-awareness and professional conduct; 3. Decision making and judgment; 4. Teaching and facilitation; 5. Environmental stewardship; 6. Program management; 7. Safety and risk management; 8. Technical ability. This unique approach to outdoor and adventure leadership will help students meet current professional standards in the field as they prepare for careers in education and recreation. The students move step by step through the materials and assignments, gaining and demonstrating leadership competencies, which they will document through a portfolio of their course experiences. The development of these portfolios is a highly practical and valuable takeaway for students looking to get a leg up as they ready themselves for their careers. This latest edition of Outdoor Leadership offers new features, material, and resources, including: The expertise and perspectives of new author Marni Goldenberg; A new chapter on program assessment; A new chapter on developing cultural and social justice competencies as an outdoor leader; A redistribution of the content on values and ethics (formerly a single chapter) across multiple chapters; An increased emphasis on international perspectives; A stronger focus on outdoor leadership in the area of ecotourism; Revisions to address critical issues in the evolving field of outdoor and adventure leadership. While primarily directed at novice outdoor leaders, Outdoor Leadership, Second Edition, is useful for more experienced outdoor leaders as well, including administrative and supervisory personnel in outdoor leadership organizations. The authors have created a balance between theory and practice as they explore the eight core competencies by doing the following: Introducing students to a wide variety of theories and concepts integral to outdoor leadership; Using chapter-opening vignettes to illustrate the theories and concepts addressed in the chapter; Acquainting readers with numerous organizations and agencies in which outdoor leaders work; Offfering a series of learning activities and professional development exercises to transform the theoretical into the practical. The result is a highly useful resource that grounds students in the theories, concepts, and competencies that they need in order to be successful leaders in outdoor and adventure settings. This competency-based approach will help aspiring outdoor leaders plan safe, enjoyable, and ecologically responsible expeditions; acquire and showcase their leadership abilities, culminating in a professional portfolio; and develop the knowledge and expertise they need to be effective leaders.